Evaluation of Yersinia enterocolitica diagnostic approaches - MM Soltan Dallal; MR Khorramizadeh; F Matin; S Eshraghi; S Jadidy; A Brahmeh; R Bakhtiary; F Saberpoor; SZ Rouhani Rankouhi (Tehran University of Medical Sciences, 2008)
Background and Aim: Yersinia enterocolitica is a Gram-negative bacterium which its strains are involved in human diseases. To differentiate among pathogenic and non-pathogenic types, tests such as Congo Red absorption, Crystal Violet, and Calcium Dependency test are used. These tests are based on existence of 70-75 kb plasmids and sometimes, with respect to plasmids instability, we will face false negative results. Therefore, by setting up a methodology based on stable chromosomal genes of pathogenic agent we can overcome this hurdle. The goal of this survey was comparison among routine and molecular diagnostic approaches in the identification of Y. enterocolitica pathogenic strains. Materials and Methods: Some Gram-negative bacteria from family Enterobacteriacea and some Y.  enterocolitica strains isolated of human beings and environment were evaluated. Results: Obtained results showed that 4 Y. enterocolitica strains isolated of human beings were PCR positive while PCR results of environmental strains, one human strain and non-Yersinia strains were negative. Conclusion: The mentioned approach can be used as a method to differentiate among pathogenic and non-pathogenic strains of Y. enterocolitica.